UPAYA PENANGANAN BERSIHAN JALAN NAPAS MELALUI MANAJEMEN JALAN NAPAS PADA PASIEN YANG MENGALAMI INFEKSI OPORTUNISTIK: LITERATUR REVIEW - Nuriya, Nuriya; Taufik , Agis (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Introduction: AIDS is a disease caused by Immunodeficiency Virus that can weaken a person's immune system and make susceptible to various diseases. TB is one of the opportunistic infections experienced by people with HIV / AIDS. Pulmonary tuberculosis often occurs a buildup of secretions that cause problems with ineffectiveness of airway cleaning so this is needed treatment that can help in removing sputum. Purpose: This study aims to conduct a literature review on some literature on the effective effects of coughing on patients with ineffectiveness of airway nets. Method: A systematic review was conducted with the PICO model in April 2022. Literature collection is done by browsing the PubMed database of (n:20) articles, Sciencedirect (n:3) articles, and Google Scholar (n:6) articles. So that the number of articles as many as 29 articles. However, only 5 articles that fit the author's inclusion criteria in the last 5 years, free full text, appropriate themes and original reviews. Keywords used: "Effective Cough", "Airway Clearance", "TUBERCULOSIS", and "HIV". Result: The influence of effective cough techniques carried out on patients with ineffectiveness of airway nets. This is evidenced by the expenditure of sputum. Conclusion: Coughing can effectively help the process of removing sputum that blocks the airway. However, further knowledge is needed with regard to the recommendation guidelines and the need to overcome obstacles in health services.